Semantical Correctness of Simulation-to-Animation Model and Rule Transformation - Ermel, Claudia; Ehrig, Hartmut; Ehrig, Karsten (Electronic Communications of the EASST, 2006)
In the framework of graph transformation, simulation rules are well-known to define the operational behavior of visual models.Moreover, it has been shown already how to construct animation rules in a domain specific layout from simulation rules.An important requirement of this construction is the semantical correctness which has not yet been considered.In this paper we give a precise definition for simulation-to-animation (S2A) model and rule transformations.Our main results show under which conditions semantical correctness can be obtained.The results are applied to analyze the S2A transformation of a Radio Clock model.Keywords: graph transformation, model and rule transformation, semantical correctness, simulation, animation